2016
DOI: 10.1016/j.nbt.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis directly from PCR: progress and applications of cell-free protein synthesis with linear DNA

Abstract: A rapid, versatile method of protein expression and screening can greatly facilitate the future development of therapeutic biologics, proteomic drug targets and biocatalysts. An attractive candidate is cell-free protein synthesis (CFPS), a cell-lysate-based in vitro expression system, which can utilize linear DNA as expression templates, bypassing time-consuming cloning steps of plasmid-based methods. Traditionally, such linear DNA expression templates (LET) have been vulnerable to degradation by nucleases pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 100 publications
0
54
0
Order By: Relevance
“…A combination of this modified cell-free method and linear template DNA, which has been studied and engineered by a number of researchers (He and Taussig, 2001, Woodrow et al, 2006, Yang et al, 1980, could facilitate rapid screening for a mutant onconase with increased potency against cancer cells. More information about using linear DNA templates and high-throughput CFPS can be found in recent reviews and papers (Murray and Baliga, 2013, Schinn et al, 2016, Yabuki et al, 2007.…”
Section: Cfps For Challenging To Express Cytotoxic Anticancer Biothermentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of this modified cell-free method and linear template DNA, which has been studied and engineered by a number of researchers (He and Taussig, 2001, Woodrow et al, 2006, Yang et al, 1980, could facilitate rapid screening for a mutant onconase with increased potency against cancer cells. More information about using linear DNA templates and high-throughput CFPS can be found in recent reviews and papers (Murray and Baliga, 2013, Schinn et al, 2016, Yabuki et al, 2007.…”
Section: Cfps For Challenging To Express Cytotoxic Anticancer Biothermentioning
confidence: 99%
“…• Open Nature  Ease of monitoring (Smith et al, 2014b)  Ease of optimization (Smith et al, 2014b)  No transport limitation (Swartz, 2012) • Higher toxicity tolerance (Casteleijn et al, 2013) • Ease of Manipulation  uAA incorporation (Zimmerman et al, 2014)  Disulfide bond formation Swartz, 2011, Goerke and  Folding using chaperones (Spirin and Swartz, 2008)  Addition of exogenous materials (Swartz, 2012) • Fast protein synthesis (Zawada et al, 2011) • Ability to use linear DNA template (Schinn et al, 2016) • High-throughput screening (Woodrow et al, 2006, Woodrow and • Scalable (Zawada et al, 2011) • Platform for personalized medicines (Kanter et al, 2007) • Lyophilization capable  Ease of stockpiling reagents (Smith et al, 2014a)  Ease of transportation (Smith et al, 2014a) • Sterilization method (Smith et al, 2015) • Not yet an FDA-approved Process • Higher reagent cost compared to in vivo systems (Swartz, 2006) • Largest industrial scale fermentation demonstrated is 100 L (Zawada et al, 2011) • Limited protein synthesis life time (typically 3-12 hours in batch format) (Michel-Rydellet et al, 2004) • Lack of cell-free specific bioreactor development reported in literatura…”
Section: Advantages Disadvantagesmentioning
confidence: 99%
“…The linear template degradation which is problematic without substantial intervention, is fairly common in cell‐free systems, as well (Jahanban‐Esfahlan et al, 2017; Seidi et al, 2018). However, LET‐based CFPS is a practical instrument for high‐throughput studies and screenings of engineered proteins (Schinn, Broadbent, Bradley, & Bundy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A minimized genetic code promises to expand the available proteomic toolset with implications in many fields, including biotherapeutics, biocatalysis, protein labeling, and minimal cells . Such a rewriting of the genetic code requires the decoupling and reengineering of the codon–tRNA–amino acid relationships, which defines the genetic coding of proteins by nucleic acids .…”
Section: Introductionmentioning
confidence: 99%